The Use of Three Dimensional Puzzle as a Media to Improve Visual-Spatial Intelligence of Children Aged 5-6 Years Old - Fitriyani, Huda; Tasuah, Neneng (Indonesian Journal of Early Childhood Education Studies, 2014)
The visual-spatial intelligence of children aged 5-6 years old becomes absolutely essential for individuals to be able to adapt well to the environment and to be successful. The purpose of this study was to determine the increase in visual-spatial intelligence of children aged 5-6 years after being treated using three-dimensional puzzle in PGRI 25 kindergarten, Karangrejo Semarang. The population was the students of PGRI Kindergarten in Gajahmungkur district that implemented the same curriculum. The sampling technique used in this study was cluster sampling, and the drawn sample was PGRI 25 Kindergarten, Karangrejo, group B as many as 30 children. The results of the study found an increase in the children’s visual-spatial intelligence, seen from the results of the first test and the second test after being given treatment. The results of the first test was a percentage of 46% and the second test was 54%. Then based on the calculation results of test I and II, there was an increase of visual-spatial intelligence by 8%. Based on that description, it can be concluded that three-dimensional puzzle can enhance the visual-spatial intelligence of children aged 5-6 years after being given treatment using three-dimensional puzzle. Teachers are advised to use this media.How to citeFitriyani, H., & Tasu’ah, N. (2014). The Use of Three Dimensional Puzzle as a Media to Improve Visual-Spatial Intelligence of Children Aged 5-6 Years Old. Indonesian Journal Of Early Childhood Education Studies, 3(1), 47-53. doi:10.15294/ijeces.v3i1.9476